Change in the sensitivity of PM-355 track detectors for protons after long–term storage. (October 2016) - Malinowska, A.; Jaskóła, M.; Korman, A.; Szydłowski, A.; Malinowski, K.; Sartowska, B.; Kuk, M.
Abstract: Changes in the sensitivity function due to fading of the tracks in CR-39/PM-355 detectors stored over a 9 – year period have been studied using protons in the energy range 0.2–6 MeV. The irradiated and non–irradiated detectors were stored in air at room temperature in the absence of light. The track diameters were found to decrease as time passed from the detector exposure to etching. The bulk etch rate VB is not affected by ageing effects and remains almost constant over a nine year period of storage. The sensitivity function V = VT /VB represents a small loss of sensitivity with storage time (about 1–2% per year). Highlights: Changes in the sensitivity function stored over a 9-year period have been studied. The sensitivity function indicates a small loss of about 1–2% per year. Results indicate that the bulk etch rate VB is almost constant. The etching procedure must be exactly reproduced.